Retraction Note: Epilepsy and the Quran Recitation as a Meditation - Çaksen, Hüseyin (Journal of Pediatric Epilepsy, 2024)
An investigation by the publisher found a number of articles, including this one, published in Journal of Pediatric Epilepsy in Volume 12, Number 02, 63-64, in June 2023 (DOI: 10.1055/s-0042-1756438), with a number of concerns, including but not limited to undeclared conflicts of interest and manipulated peer review procedures. As a result, the publisher has retracted and removed this article.